2021
DOI: 10.3390/foods10020434
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid and Carotenoid Ester Profile and Their Deposition in Plastids in Fruits of New Papaya (Carica papaya L.) Varieties from the Canary Islands

Abstract: The carotenoid profile of non-saponified and saponified extracts of different tissues (pulp and peel) of fruits of three new papaya varieties, Sweet Mary, Alicia, and Eksotika, was characterized for the first time, and almost all carotenoid compounds were quantified. Carotenoids and carotenoid esters were analyzed and characterized using HPLC–photo diode array (PDA–MS with atmospheric pressure chemical ionization with positive ion mode (APCI+) with a C30 reversed-phase column. The carotenoid deposition in coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
14
0
2
Order By: Relevance
“…The complete characterization of carotenoids and carotenoids esters from papaya cv. Sweet Mary tissues (pulp and peel) using the convectional extraction has been previously reported by Lara-Abia et al [2], and this information was the guide to identify the carotenoids and carotenoids esters extracted to the vegetable oils. The chromatographic identification (retention time (min), compound identity, absorption maxima (nm), %III/II, %A b /A ii , [M + H] + (m/z), and MS fragmentation pattern (m/z) of each lipophilic carotenoid compound found in oil vegetable extracts is described in Table 1.…”
Section: Carotenoid Uae From Papaya Pulp and Peel Using Vegetable Oilsmentioning
confidence: 85%
See 2 more Smart Citations
“…The complete characterization of carotenoids and carotenoids esters from papaya cv. Sweet Mary tissues (pulp and peel) using the convectional extraction has been previously reported by Lara-Abia et al [2], and this information was the guide to identify the carotenoids and carotenoids esters extracted to the vegetable oils. The chromatographic identification (retention time (min), compound identity, absorption maxima (nm), %III/II, %A b /A ii , [M + H] + (m/z), and MS fragmentation pattern (m/z) of each lipophilic carotenoid compound found in oil vegetable extracts is described in Table 1.…”
Section: Carotenoid Uae From Papaya Pulp and Peel Using Vegetable Oilsmentioning
confidence: 85%
“…The chromatographic profiles of the papaya pulp and peel extracts obtained from the standard (control) untreated and UAE extracts did not show any differences in carotenoid profiles between using soybean oil and sunflower oil (Figure S1, Supplementary material). In Figure S1, the chromatograms corresponded to the carotenoid profile of UAE extracts obtained at the optimum conditions (high yields) and to the control extracts obtained by the standard protocol for carotenoid analysis [2]. No degradation of carotenoids or carotenoid esters was detected in the UAE extracts, thus carotenoid profiles remained unchanged throughout the extraction process.…”
Section: Carotenoid Uae From Papaya Pulp and Peel Using Vegetable Oilsmentioning
confidence: 97%
See 1 more Smart Citation
“…The identification and quantification of carotenoids and carotenoid esters on the pulp tissue of the Sweet Mary, Alicia and Eksotika papaya varieties has been previously reported by Lara-Abia et al [13]. The results reported in the mentioned investigation were considered as the control data for this study due to the simultaneity of the two studies.…”
Section: Individual Carotenoid Profile In Papaya Tissuesmentioning
confidence: 78%
“…The promotion of this fruit and its nutritional benefits are, therefore, key to support the import and demand of papaya fruits, especially in the European Union. In Spain, the introduction in the market of three new papaya varieties, i.e., Sweet Mary, Alicia and Eksotika, cultivated in the Canary Islands, has caught the interest in our research group due to their interesting carotenoid profile based on a recent study reported by Lara-Abia et al [13], where the utilization of these new varieties as a source of bioactive compounds is a real possibility for industrial applications.…”
Section: Introductionmentioning
confidence: 99%